2020
DOI: 10.1093/tas/txaa146
|View full text |Cite
|
Sign up to set email alerts
|

Chromium propionate supplementation alters animal growth performance, carcass characteristics, and skeletal muscle properties in feedlot steers

Abstract: The objective of this study was to evaluate the effects of increasing concentrations of Cr propionate (CrP) on feedlot performance, blood parameters, carcass characteristics, and skeletal muscle fiber properties in feedlot steers. Crossbred steers (n=32; 367±2.5 kg; 16 pens; 2 hd/pen) were blocked by BW, and treatment was randomly assigned to pen: 1) 0 mg added Cr/kg diet DM (control), 2) 0.15 mg added Cr/kg diet DM (Cr propionate (CrP); KemTRACE® Chromium 0.04%, Kemin Industries, Des Moines, IA), 3) 0.30 mg a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Bernhard et al [13] detected no differences for serum GLS concentrations sale barn acquired steers supplemented with Cr as chromium propionate at 1 h postprandial after 56 d of supplementation. Likewise, [14] detected no differences in sera parameters when CrP was fed. 1 No added Cr "CON"; added 0.4 mg•kg −1 Cr to the total diet on a DM basis "CrP" (Kem-TRACE 0.4% Chromium Propionate, Kemin Industries, Des Moines, IA).…”
Section: Plasma Constituentsmentioning
confidence: 81%
“…Bernhard et al [13] detected no differences for serum GLS concentrations sale barn acquired steers supplemented with Cr as chromium propionate at 1 h postprandial after 56 d of supplementation. Likewise, [14] detected no differences in sera parameters when CrP was fed. 1 No added Cr "CON"; added 0.4 mg•kg −1 Cr to the total diet on a DM basis "CrP" (Kem-TRACE 0.4% Chromium Propionate, Kemin Industries, Des Moines, IA).…”
Section: Plasma Constituentsmentioning
confidence: 81%
“…Notably, when assessing the complete study period (81 d) in terms of productive behavior, no significant differences were found between the groups of pigs that received a diet supplemented with CrMet-S, CrMet-L, and RAC, suggesting an approximation of the effects of CrMet to those of RAC on productive behavior. However, improvement in the ADG and final BW of the pigs could be attributed to an increase in protein synthesis in the tissue of their skeletal muscle induced by organic Cr (CrMet) [ 11 , 15 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, research with Cr supplementation to feedlot cattle is inconsistent by Cr source and inclusion level. Long-duration feeding of Cr propionate, with a range of Cr inclusion rates (0.25 mg Cr/kg DM to 0.45 mg Cr/kg DM), demonstrated increased live weight gain ( Barajas et al, 2008 ; Baggerman et al 2020 ; Hallmark et al, 2020 ) and carcass weight ( Barajas et al, 2008 ; Budde et al, 2019 ; Baggerman et al, 2020 ; Hallmark et al, 2020 ). Yet, Cr propionate fed in combination with yeast products, providing 3.2 mg Cr/steer daily did not show a difference from control for feedlot growth or carcass characteristics ( Van-Bibber Kruger et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over 80% of skeletal muscle tissue relies upon insulin-dependent glucose uptake mechanisms ( McGilcrest et al 2011 ). The role of Cr in protein synthesis was demonstrated by Baggerman et al (2020) ; feedlot steers fed 0.45 mg/kg DM Cr propionate had an increased upregulation of glucose transporter type-4 in skeletal muscle tissue compared with control, and a subsequent increase in hot carcass weight. Type-4 glucose transporters are insulin-dependent receptors and are responsible for shuttling extracellular glucose into adipose and muscle tissue ( Sano et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation